Optimization of bioethanol from oil palm frond juice by using saccharomyces cerevisiae - Siti Hajar, Mat Zani (2018)
Considered to be the environmental-friendly liquid fuel, bioethanol can be a reliable renewable source of energy to substitute fossil fuels. Bioethanol fermentation became an ongoing interest among researcher to find out ways to produce an alternative energy by microbial fermentation in which can be produced by direct fermentation of sugar components of plant materials. This study focused on the utilization of oil palm frond (OPF) juice as sustainable source of fermentation products as it’s have high sugar contents and easily obtained daily in Malaysia. OPF juice was used as the carbon source for the effective bioethanol production by the yeast Saccharomyces cerevisiae Kyokai No. 7 (ATCC 26622). Based on the sugar analysis using High Performance Liquid Chromatography (HPLC), it showed that the total sugars concentration in OPF juice used throughout the study was 56.87 g/L. In order to further evaluate the best condition of parameters which affecting the production of bioethanol, investigation on the effect of temperature, medium initial pH and agitation speed was carried out by using One-Factor-At-Time (OFAT) method. This was followed by optimizing the fermentation process of bioethanol production using response surface methodology (RSM) to explore the response pattern and accurate values of the fermentation parameters. A five-level-three-factor central composite design (CCD) was attempted in this study and the central point of each process variable was chosen based on the best condition obtained from the OFAT method. The parameters range were set as follows; medium initial pH (5-9), temperature (27.5-37.5°C), and agitation speed (80-120 rpm). Bioethanol and residual sugars concentration were determined by using HPLC analysis. The optimum conditions for bioethanol production were proposed to be medium initial pH (6.60), temperature (33°C) and agitation speed (96 rpm). Based on the validation experiment, the optimum bioethanol yield was 0.50 ±0.02 g/ g sugars and this value was in close agreement with the model prediction where the difference was only 4.17%. Under the optimal conditions, the bioethanol yield obtained was 47.06% higher compared with non-optimized condition. Repeated batch of bioethanol production was carried out at larger scale by using 2-L bioreactor to study the performance of S. cerevisiae for long term experiment to mimic a long term industrial bioethanol production process. For the repeated batch experiment, results showed that highest bioethanol yield at agitation speed of 50 rpm, drain (fermentation broth) and fill (fresh OPF juice) volume at 75% and ten cycles of repeated batch. The average bioethanol yield of ten successive batches at 75% drain and fill volume were 0.41 g/ g sugars. As a conclusion, the present research has shown that OPF juice is promising to be used as a renewable and complete fermentation feedstock for bioethanol production to support the biotechnology industry.